Analisis Pengaruh Upah dan Tingkat Pendidikan Terhadap Pasar Tenaga Kerja Indonesia: Perspektif Ekonomi Islam - Wati, Risma; Ermawati , Liya; Nuraziza, Sania (ARBITRASE: Journal of Economics and Accounting, 2025)
The research is used to analyze the effect of minimum wage, educated labor and uneducated labor on the labor market in Indonesia in the perspective of Islamic economics for the period 2010-2024. This research focuses on Indonesia in a period of 15 years, starting from 2010-2024. This research focuses on Indonesia over a period of 15 years, starting from 2010-2024. All data used is obtained from the official website of the Indonesian Central Bureau of Statistics (BPS) and uses quantitative methods, and uses explanatory research as a research methodology. The author uses Eviews 10 technology to facilitate data processing. This research uses the Vector Error Correction Model (VECM) approach with the data used focused on Indonesia from 2010 to 2024 taken from the official website of BPS Indonesia. This study aims to gain an understanding of the causal relationship between the independent variables and the dependent variable (Y) Labor Market, the independent variables are (X1) Minimum Wage, (X2) Educated Labor and (X3) Uneducated Labor. The result obtained from this research is that the minimum wage has a significant negative effect in the long run on the labor market (coefficient value -7.48E-05), and has no effect in the short run on the labor market (coefficient value 2.06E-06). Educated labor has a positive significant effect in the long run on the labor market (coefficient value 2.40E05), but has no effect in the short run on the labor market (coefficient value -904E-08). Similar to the minimum wage, uneducated labor has a negative significant effect in the long run on the labor market (coefficient value -1.91E05), and has no effect in the short run (coefficient value 4.57E-09).